Kingdom of the Netherlands-Netherlands : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2011)
The Netherlands has a long-standing legal framework concerning Anti-Money Laundering and Combating the Financing of Terrorism preventive measures, which dates back to 1993. The legal framework for Customer Due Diligence is generally adequate; however, a number of provisions are problematic. The Dutch system of preventive measures emphasizes the risk-based approach, complemented by a principles-based approach. The principles-based approach should be better supported with guidance for financial institutions. Although most elements of the Suspicious Transaction Report reporting requirements are in place, the reporting regime has one minor legal shortcoming and raises effectiveness concerns.